2020
DOI: 10.18632/oncotarget.27503
|View full text |Cite
|
Sign up to set email alerts
|

Targeting PI3Kβ alone and in combination with chemotherapy or immunotherapy in tumors with PTEN loss

Abstract: Background: PTEN-deficient tumors are dependent on PI3Kβ activity, making PI3Kβ a compelling target. We evaluated the efficacy of PI3Kβ inhibitor AZD8186 on tumors with PTEN loss. Results: In vitro cell viability assay and immunoblotting demonstrated that PTEN loss was significantly correlated with AZD8186 sensitivity in triple negative breast cancer (TNBC) cell lines. Colony formation assay confirmed sensitivity of PTENdeficient cell lines to AZD8186. AZD8186 inhibited PI3K signaling in PTEN loss TNBC cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 37 publications
(51 reference statements)
0
15
0
Order By: Relevance
“…A phase I clinical trial (NCT01884285) is also studying the PI3KCB/PI3KCD inhibitor AZD8186 in patients with TNBC and known PTEN-deficient/-mutated or PIK3CB-mutated/-amplified advanced tumors and in combination with abiraterone acetate or AZD2014, an mTOR inhibitor [ 104 ]. AZD8186 has single-agent efficacy in PTEN-deficient TNBC cell lines in vitro, but has limited single-agent efficacy in vivo [ 105 ]. However, AZD8186 showed enhanced efficacy when combined with paclitaxel and anti-PD1 in vivo [ 105 ].…”
Section: Pi3k Pathway Inhibition In Her2+ and Triple-negative Breast Cancer Subtypesmentioning
confidence: 99%
See 1 more Smart Citation
“…A phase I clinical trial (NCT01884285) is also studying the PI3KCB/PI3KCD inhibitor AZD8186 in patients with TNBC and known PTEN-deficient/-mutated or PIK3CB-mutated/-amplified advanced tumors and in combination with abiraterone acetate or AZD2014, an mTOR inhibitor [ 104 ]. AZD8186 has single-agent efficacy in PTEN-deficient TNBC cell lines in vitro, but has limited single-agent efficacy in vivo [ 105 ]. However, AZD8186 showed enhanced efficacy when combined with paclitaxel and anti-PD1 in vivo [ 105 ].…”
Section: Pi3k Pathway Inhibition In Her2+ and Triple-negative Breast Cancer Subtypesmentioning
confidence: 99%
“…AZD8186 has single-agent efficacy in PTEN-deficient TNBC cell lines in vitro, but has limited single-agent efficacy in vivo [ 105 ]. However, AZD8186 showed enhanced efficacy when combined with paclitaxel and anti-PD1 in vivo [ 105 ]. Further study is needed to determine the optimal combination therapies for PTEN-deficient breast cancer.…”
Section: Pi3k Pathway Inhibition In Her2+ and Triple-negative Breast Cancer Subtypesmentioning
confidence: 99%
“…In 2020, Owusu-Brackett et al reported a study, in which in vitro cell viability assay and immunoblotting indicated that PTEN loss was related to AZD8186 sensitivity in TNBC [ 29 ]. Colony formation assay was also studied and confirmed the sensitivity of PTEN deficient cell lines to AZD8186.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, AKT inhibition can led to a favorable immune profile in the breast tumor microenvironment, including an increased density of CD3+CD8+ cells and better expression of interferon genes, providing a rationale for using AKT inhibition plus immunotherapy combination ( Marks et al, 2020 ). Correspondingly, the PI3Kβ inhibitor AZD8186 enhanced anticancer efficacy by combining with anti-PD1 Ab in PTEN-deficient xenografts ( Owusu-Brackett et al, 2020 ). Combining nanoscale PI3K-targeting supramolecular therapeutics with anti-PD-L1/PD-1 Ab exhibited a synergetic anticancer effect in breast cancer in vivo ( Kulkarni et al, 2016 ).…”
Section: Pi3k/akt/mtor Pathway Induces Drug Resistance In Breast Cancmentioning
confidence: 99%